Analisis Pengaruh User Experience (UX) dan Trust terhadap Re-purchase Intention pada Platform Marketplace menggunakan Model Technology Acceptance Model (TAM) - Bimo Febriyanto; Sakti Maulana; Libra Seftian Pri Utami (Journal of Science, Technology, and Innovation, 2025)
The rapid growth of marketplace platforms has intensified competition, shifting managerial focus from user acquisition to retention and re-purchase intention. This study aims to analyze the influence of User Experience (UX) and trust on re-purchase intention within marketplace platforms using the Technology Acceptance Model (TAM) as the analytical framework. A quantitative explanatory approach was employed, with data collected through structured questionnaires distributed to active marketplace users who had conducted repeated transactions. The constructs of UX, trust, perceived ease of use, perceived usefulness, and re-purchase intention were analyzed to examine their interrelationships. The findings indicate that UX significantly influences perceived ease of use and perceived usefulness, which subsequently shape users’ acceptance of marketplace technology. Trust plays a critical role in strengthening users’ attitudes toward the platform by reducing perceived risk and enhancing confidence in system security and reliability. The integration of UX and trust demonstrates a synergistic effect in driving re-purchase intention, highlighting that positive digital experiences must be supported by strong user trust to sustain long-term transactional behavior